ANÁLISIS DE LA SITUACIÓN ACTUAL EN EL REGISTRO DE PATENTES POR PARTE DE LAS UNIVERSIDADES EN MÉXICO - Marco Tulio Cerón; Lourdes del Carmen Pineda; Beatriz Pico; Manuel González (European Scientific Journal, ESJ, 2014)
A patent is an indicator variable of inventions and innovations. At the same time is a parameter in the production and generation of scientific knowledge in Universities. According to data issued by the IMPI in 2013, received 15,444 requisitions for patent registration. Of the 1,211 requisitions they were made by Mexican entities, representing 7.8% of the applications submitted. This work analyzes the current situation of patenting and as a result thereof, manifests the need to create a methodologyforrecordingthem.